(untitled) (Revista Brasileira Multidisciplinar, 2019)
According to the current legislation in Brazil, Environmental Education must be worked in all areas of education, across all disciplines, through transversality. However, some teachers do not have the appropriate training to work on the subject or simply do not find it important, leaving it aside. With the intention of getting to know the teachers’ perspective on Environmental Education, an interview was carried out in order to understand their habits and difficulties about the theme, orienting them towards continuing education.